2015
DOI: 10.1515/msp-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and characterization of Ag1/2Al1/2TiO3 nanoceramics

Abstract: Single phase silver aluminum titanate (Ag 1/2 Al 1/2 )TiO 3 , later called AAT, nanoceramic powder (particle size 2 to 7.5 nm) was synthesized by a low-cost, green and reproducible tartaric acid gel process. X-ray, FT-IR, energy dispersive X-ray and high resolution transmission electron microscopy analyses were performed to ascertain the formation of AAT nanoceramics. X-ray diffraction data analysis indicated the formation of monoclinic structure having the space group P2/m(10). UV-Vis study revealed the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Therefore, the synthesis of pure and homogeneous material is a subject of great importance. It has been observed that ceramic materials synthesized using different soft-chemical methods exhibited improved properties compared to the same prepared by traditional solid state reaction method [3,4,[9][10][11][12][13]. One such lead-free ceramic in this series is perovskite (Fe 1/2 Ag 1/2 )TiO 3 which is mechanically tough and ensure environment-friendly applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the synthesis of pure and homogeneous material is a subject of great importance. It has been observed that ceramic materials synthesized using different soft-chemical methods exhibited improved properties compared to the same prepared by traditional solid state reaction method [3,4,[9][10][11][12][13]. One such lead-free ceramic in this series is perovskite (Fe 1/2 Ag 1/2 )TiO 3 which is mechanically tough and ensure environment-friendly applications.…”
Section: Introductionmentioning
confidence: 99%